Inferior Longitudinal Fascicle and Reading: Exploring Their Relationship Through a Brain Stimulation Case Study. (November 2022) - Papatzalas, Christos; Papathanasiou, Ilias; Paschalis, Thanasis; Tzerefos, Christos; Kapsalaki, Eftychia; Petsiti, Argyro; Fountas, Kostas
Awake brain surgery allows for maximal tumor resection, while minimizing postoperative deficits, even when the tumor is located within eloquent brain regions. In the current study, we present the case of a patient who underwent awake craniotomy to remove a space-occupying lesion located at the left (dominant) temporal lobe. During subcortical mapping, electrical stimulation of the inferior longitudinal fasciculus caused severe errors (paralexias) on a semantic odd-word out task but not on other tasks that use different input routes and processes. The cognitive neuropsychological model for single word processing assisted us to associate a specific structure (inferior longitudinal fascicle [ILF]) with a specific cognitive process (i.e., access to the semantic system). Our results highlight the importance of subcortical fascicles in reading and agree with previous studies regarding the critical role of ILF in reading comprehension.